Princeton readings in Islamist thought texts and contexts from al-Banna to Bin Laden - Euben, Roxanne Leslie; Zaman, Muhammad Qasim (Princeton University Press, 2009)
This anthology of key primary texts provides an unmatched introduction to Islamist political thought from the early twentieth century to the present, and serves as an invaluable guide through the storm of polemic, fear, and confusion that swirls around Islamism today.